Increased blood levels of persistent organic pollutants (POP) in obese individuals after weight loss—A review. (2nd January 2017) - Jansen, Aina; Lyche, Jan L.; Polder, Anuschka; Aaseth, Jan; Skaug, Marit Aralt
ABSTRACT: Lipophilic persistent organic pollutants (POP) are stored in adipose tissue. Following rapid weight loss such as when induced by bariatric surgery, an increased release of potential harmful lipophilic compounds into the blood circulation may occur. Weight reduction is recommended for overweight and obese individuals in order to decrease risk of weight-related health problems. However, in cases of significant weight reduction POP become mobilized chemicals and consequently may adversely affect health, including endocrine disruption. The objective of the present investigation was to estimate quantitatively the level of mobilization of POP following weight loss over time. According to literature search criteria, 17 studies were identified with 2061 participants. Data from 5 of the studies with 270 participants were used to assess the change in blood levels of POP in percent per kilogram weight loss. Weight loss in the included studies varied from 4.4 to 64.8 kg. In all studies, the majority of POP concentrations in blood were found to rise following weight reduction. Blood concentrations following weight reduction were elevated by 2–4% per kilogram weight loss for most POP examined. The increased POP levels were still elevated 12 mo after intervention. Most research in this field, including animal studies, is carried out on a single compound or group of selected compounds, not taking the "cocktail effect" into consideration. This does not reflect the true range of POP to which humans are actually exposed. Few chronic investigations have been published and, in particular, few studies were available that compared the increase in POP concentrations with clinical consequences as individuals lost weight. These limitations call for caution in interpreting results. The benefits of losing weight still far outweigh the potential adverse health risks. However, further studies are recommended to determine the clinical significance of increased blood levels of POPs following rapid and excessive weight loss, particularly for women attending weight reduction treatment before pregnancy.